Desarrollo y política indígena en el Alto Yuruá (frontera Brasil-Perú) - Pimenta, José (2022)
The Rio Amonia Ashaninka indigenous people live in the Brazilian state of Acre on the Upper Jurua River on the border between Brazil and Peru. After their struggle against intensive lumber activities in the 1980s, andhaving obtained the demarcation of their territory in the early 1990s, they engaged in strategic alliances with several partners as an attempt to find economic alternatives to lumbering. In the past twenty years, withthe growing influence of environmental concerns regarding development in the Amazon, the Amonia Ashaninka acquired great political visibility through various projects geared to the paradigm of «sustainable development ». Based on ethnographic fieldwork, carried out in various stages over the last fifteen years with the Amonia Ashaninka, this article retraces the plight of this community in the past two decades for land demarcation and to establish interethnic and transfrontier alliances as a means to install a broad «sustainable development» policy for the entire Upper Jurua region. It also analyses the present day development and border policies of both the Brazilian and Peruvian states, which entail new threats to the region’s indigenous peoples.